Analysis of the Effect of Monitoring Tools and Automation of Temperature Control on Static Inverter Panel Power of Railbus Batara Kresna - Putra, Muhammad Arjuna Anggara Putra; Amalia, Zakiyah (International Journal of Frontier Technology and Engineering, 2024)
The Static Inverter Panel is an electrical device designed to process electrical energy from the Railbus Batara Kresna generator to produce an output that meets the railbus’s requirements. The static inverter panel often experiences cut-off due to excessively high panel temperatures. The static inverter panel will not operate until the temperature falls within the permissible specification limits, which is below ±70°C. The power of the static inverter panel must always be maintained to ensure the optimal performance of the railbus’s electrical system. The purpose of this study is to understand the impact of panel temperature and room temperature on the power of the static inverter panel. The study was conducted by developing a monitoring and automatic temperature control device that will regulate the static inverter panel’s temperature. Data processing was performed by observing the graphs from each test. The study results indicate that as the panel temperature increases from 30.8°C to 47.6°C in the morning and afternoon, the panel power decreases. An increase in room temperature from 31.8°C to 38.0°C in the morning also causes a decrease in power. However, an increase in room temperature from 38.0°C to 42.5°C in the afternoon causes irregular changes in power.